Case report: First case of neuromelioidosis in Europe: CNS infection caused by Burkholderia pseudomallei - Dimitriou, Nikolaos G.; Flüh, Greta; Zange, Sabine; Aytulun, Aykut; Turowski, Bernd; Hartung, Hans-Peter; Meuth, Sven G.; Gliem, Michael (Frontiers in Neurology, 2022)
Neuromelioidosis is a rare CNS infection caused by Burkholderia pseudomallei and is characterized by high morbidity and mortality. Our report presents the diagnostic and therapeutic approach of the first case of neuromelioidosis confirmed in Europe. A 47-year-old man with a medical history of recurrent otitis with otorrhea and fever after tympanoplasty and radical cavity revision operation on the left ear was admitted with headache, decreased level of consciousness, dysarthria, left-sided hemiparesis, and urinary incontinence. After extensive investigations including MRI, microbiological, serological, and CSF analyses, and, ultimately, brain biopsy, a diagnosis of neuromelioidosis was established. Despite antibiotic treatment, the patient showed no clinical improvement and remained in a severely compromised neurological state under mandatory mechanical ventilation. Neuromelioidosis can pose a diagnostic challenge requiring an extensive diagnostic evaluation because of its uncommon clinical and radiological presentations.